In‐operando crystallization study of zinc nitrate hexahydrate using zinc oxide nucleators. Issue 6 (14th June 2022) - Chakraborty, Anirban; Noh, Juran; Shamberger, Patrick; Yu, Choongho
Abstract: Supercooling (∆TSup ) is one of the crucial problems in utilizing a phase change material (PCM), which has been attempted to overcome using nucleators possessing small lattice disregistry without comprehensive understanding of the nucleation phenomenon. Here, this work studies the interactions between nucleators and PCM via in‐operando direct visualization for the first time, to the best of our knowledge, to better understand the crystallization process during freezing of a PCM using zinc nitrate hexahydrate (ZNH) and a zinc oxide (ZnO) nucleator. According to our in‐operando study, freezing was randomly initiated by only a fraction of the nucleator particles during each thermal cycling. However, previously unresponsive nucleators also suddenly crystalized PCM when the propagating crystal encountered them, improving the crystal initiation and thereby ∆TSup . Consequently, for equal wt% of ZnO, better nucleation behavior was obtained using uniformly distributed small nucleator particles throughout the PCM, as compared to either large or poorly distributed aggregated nucleators. DSC results using ZnO‐needle as nucleator confirmed a 38% and 33.3% lower ∆TSup upon employing 5 wt% small (individual) particles ( 4 μm on average), as compared to using equal wt% of small (aggregated) particle clusters ( 200 μm) and large particles ( 46 μm), respectively. Crystallization of ZNH caused additional hair‐like ZnO growth preferentially decorated along lateral faces of the original nucleator particles. The in‐operando studies are valuable tools to correlate inherent crystallization phenomena to the practical thermal energy storage properties of the system.